Thermodynamic Control of Small RNA-Mediated Gene Silencing - Ui-Tei, Kumiko; Nishi, Kenji; Takahashi, Tomoko; Nagasawa, Tatsuya (Frontiers in Genetics, 2012)
Small interfering RNAs (siRNAs) and microRNAs (miRNAs) are crucial regulators of posttranscriptional gene silencing, which is referred to as RNA interference (RNAi) or RNA silencing. In RNAi, siRNA loaded onto the RNA-induced silencing complex (RISC) downregulates target gene expression by cleaving mRNA whose sequence is perfectly complementary to the siRNA guide strand. We previously showed that highly functional siRNAs possessed the following characteristics: A or U residues at nucleotide position 1 measured from the 5’ terminal, four to seven A/Us in positions 1–7, and G or C residues at position 19. This finding indicated that an RNA strand with a thermodynamically unstable 5’ terminal is easily retained in the RISC and functions as a guide strand. In addition, it is clear that unintended genes with complementarities only in the seed region (positions 2–8) are also downregulated by off-target effects. siRNA efficiency is mainly determined by the Watson-Crick base-pairing stability formed between the siRNA seed region and target mRNA. siRNAs with a low seed-target duplex melting temperature (Tm) have little or no seed-dependent off-target activity. Thus, important parts of the RNA silencing machinery may be regulated by nucleotide base-pairing thermodynamic stability. A mechanistic understanding of thermodynamic control may enable an efficient target gene-specific RNAi for functional genomics and safe therapeutic applications.